PENERAPAN AUTHENTIC ASSESSMENT BERBASIS E-LEARNING DALAM PEMBELAJARAN BIOLOGI - Arjaya, Ida Bagus Ari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2018)
Digital literacy occupies the latest issue in the education system of the 21st century. Global competition causes each student must be able to manage and find of well information resources. Digital literacy itself is defined as the competence used by learners to participate fully in the learning process by involving knowledge, skills and attitudes that are effective in the utilization of digital devices. Furthermore, Unesco (2017) defines digital literacy as a life skill to support lifelong education, cross national curriculum, enhances learner participation, and enhances teacher professionalism through innovative learning such as e-learning. The deeper implementation of digital literacy can be done by giving students authentic tasks accompanied by their authentic judgments. As one of the integrals of science, biology is a branch of science that focuses the object of observation on the phenomena of living things. Generally, in biology learning process used conventional assignment and paper and pencil test assessment so the learning becomes monotonic and support rote learning. One alternative way to integrate the authentic assessment component, learning and it utilization of digital literacy is to implement e-learning with authentic assessment in biology learning process. This scientific article is intended to analyze: 1) types of authentic assessment types in biology learning, 2) integration of e-learning based authentic assessment to support the biology learning process.